Trends in the Implementation of Brain-Based Learning in Indonesia: A Systematic Literature Review - Waliyyatu Azzahra; Dimas Febriansyah Krisna Dwiputra (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2023)
Understanding the brain's mechanisms underlying the learning process holds the potential to revolutionize educational strategies and designs, thereby optimizing the learning experience. Building upon this premise, this study aims to critically review and summarize the evidence of the previous studies that pinpointed the development of the brain-based learning learning implementation in Indonesia and its impact on the learning process . This study applies the systematic literature review method by following the PRISMA 2021 guidelines. We used Scopus and Google Scholar databases from 2013-2022 as the sources. Of the total 2013 articles found, only 92 met the predetermined criteria and then content analysis was carried out. The findings in this study include: (1) there was an increase in research trends related to the implementation of brain-based learning in Indonesia from 2013-2019, but it started to decline in 2020-2022; (2) quasi-experiment dominates the method used; (3) brain-based learning is relevant to be applied at various levels of education; (4) the majority of studies are conducted in the fields of mathematics and science; and (5) the application of brain-based learning has a positive impact on various aspects of learning. Based on these findings, this research provides a scientific contribution as a basis for stakeholders in developing research related to the application of brain-based learning by utilizing methods, educational levels, and fields of knowledge that have not been widely explored. This effort was carried out to encourage novelty in brain-based learning research because its application has been proven to provide various benefits for improving the quality of education in Indonesia.